CHARACTERISTICS OF ASPIRING ACCOUNTANTS OF ENTERPRISE: EVIDENCE FROM NAKHON RATCHASIMA, THAILAND - Apisithpinyo, Benjamas; BURINWATTANA, Sukritta (Asian Administration and Management Review, 2023)
The objectives of this research are to study the desired level of accountant attributes among entrepreneurs and compare the desired attributes across different business operation models. This is the quantitative research utilizing questionnaires as the research tool. The sample consists of 300 businesses located in Nakhon Ratchasima, Thailand. Statistical analysis, including frequency distribution, percentages, means, standard deviations, and one-way ANOVA, is employed for the data analysis. The findings reveal that entrepreneurs in Nakhon Ratchasima, overall, desire accountant attributes that prioritize professional values, ethics, and attitudes the most, followed by professional skills, technical competence and technological proficiency, respectively. When comparing the desired accountant attributes among different business operation models, significant differences were found at a significance level of 0.05. Specifically, manufacturing businesses require accountants with higher levels of accounting skills, technical competence, professional values, ethics, attitudes, and technological proficiency compared to businesses in the merchandise and service sectors.